2010
DOI: 10.1111/j.1476-5381.2010.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide, superoxide and peroxynitrite in the anti‐arrhythmic effects of preconditioning and peroxynitrite infusion in anaesthetized dogs

Abstract: Background and purpose: Both ischaemia preconditioning (PC) and the intracoronary infusion of peroxynitrite (PN) suppress ischaemia and reperfusion (I/R)-induced arrhythmias and the generation of nitrotyrosine (NT, a marker of PN). However, it is still unclear whether this latter effect is due to a reduction in nitric oxide (NO) or superoxide (O2 -) production. Experimental approach: Dogs anaesthetized with chloralose and urethane were infused, twice for 5 min, with either saline (control) or 100 nM PN, or sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 53 publications
8
49
0
Order By: Relevance
“…This protection against arrhythmias was similar to that we have obtained previously in the same model with ischaemic preconditioning (Végh et al, 1992a), and with the administration of NO donors (Gyorgy et al, 2000;Gonczi et al, 2009;Kiss et al, 2010). Furthermore, the present study confirmed the role of eNOS activation in the antiarrhythmic effect of simvastatin, since both the phosphorylation of eNOS (determined by Western blot) and Fluorescence intensity (arbitrary units) Fig.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This protection against arrhythmias was similar to that we have obtained previously in the same model with ischaemic preconditioning (Végh et al, 1992a), and with the administration of NO donors (Gyorgy et al, 2000;Gonczi et al, 2009;Kiss et al, 2010). Furthermore, the present study confirmed the role of eNOS activation in the antiarrhythmic effect of simvastatin, since both the phosphorylation of eNOS (determined by Western blot) and Fluorescence intensity (arbitrary units) Fig.…”
Section: Discussionsupporting
confidence: 79%
“…6). We have previous evidence that the preservation of NO bioavailability during coronary artery occlusion by preconditioning or by donating NO attenuates the reperfusion-induced marked increases of superoxide production (Kiss et al, 2010). Furthermore, the fact that L-NAME prevented the simvastatin activated enzyme to form NO (inhibits the L-arginine-NO pathway without affecting enzyme phosphorylation) and attenuated or even abolished most of the salutary effects of simvastatin, supports the hypothesis that the eNOS activated NO formation plays a crucial role in the protective effect of simvastatin against arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations